Antero-posterior reconstruction during robot-assisted radical prostatectomy: The VV technique - M. Valerio; R. Diamand; N. Grilo; R. Van Velthoven (Urology Video Journal, 2023)
Objective: To describe a simplified antero-posterior reconstruction using a single suture during robot assisted radical prostatectomy (RARP). Patients and surgical procedure: We retrospectively evaluated the functional and oncological outcomes of the first 100 consecutive patients undergoing the index technique. RARP was performed in a standardised fashion combining a posterior approach, an antegrade nerve-sparing and an extended pelvic bilateral node dissection when clinically indicated. An antero-posterior reconstruction using a double arm barbed suture, named VV by its shape, was performed at the time of the urethra-vesical anastomosis carried out according to the Van Velthoven technique. Functional and oncological outcomes are reported Results: Median age was 64 years (IQR 59–67) and median PSA was 7.8 ng/ml (6–12.1). 7%, 66% and 27% subjects were considered low, intermediate and high risk, respectively. 36% had extracapsular extension and/ or seminal vesicle invasion at final pathology. 5% required prolonged catheterisation time due to a leak at the first cystogram performed after a median of 10 days (7–11). After a median follow-up after surgery of 12 months (9–24), social continence, full continence and potency were achieved in 95%, 93% and 45%, respectively. No patient developed strictures or bladder neck contractures. Conclusion: We have shown that in this quality control study a simplified antero-posterior reconstruction mirrors the outcomes reported with more complex techniques. A formal evaluation against a relevant control group is needed to confirm these findings